Perancangan Sistem Informasi Pasien Klinik XYZ Berbasis Web - Ardiyani, Amalia; Dwita Urip Natasa; Fadila Nur Kamala; Raden Bagus Bambang Sumantri (STMIK KAPUTAMA, 2024)
The development of information technology has become an important need in all fields. This also applies to companies operating in the health sector. Technological developments in the world of health services have had a huge impact, because in the health sector it is now mandatory to use information systems to streamline operational processes. The health information system is an integrated system that is capable of managing public data and information (government, community and private) at all levels of government to support effective health development systematically. The need for accurate data/information is increasing, but it seems that the current information system is still unable to provide accurate, complete and timely data. The research methodology used at this research stage begins with analysis to find the main problems and solutions that will be implemented, the system design will be created using Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD) data. can improve the performance and experience of medical services at Clinic XYZ.